EPIDEMIOLOGICAL PREVALENCE ESTIMATES OF HYPERTENSION OF 856, 878 ADULTS IN GLASGOW. (April 2021) - Lip, Stefanie; Mccallum, Linsay; Strachan, Kylie; Mckinstry, Brian; Webb, David; Padmanabhan, Sandosh
Abstract : Objective: Systematic reviews estimate the prevalence of hypertension in high income countries to be 28.5%, with 55.6% of hypertensives on treatment and 28.4% of those on treatment having controlled hypertension. We used these estimates to determine the proportion of untreated hypertensives in the Greater Glasgow and Clyde population and to evaluate if the estimated proportion of untreated hypertension translated into increased CV mortality. Design and method: Dispensed prescription and mortality data were obtained on 856, 878 adults who attended either primary care or secondary care in the NHS Greater Glasgow and Clyde area between 2010 and 2016. Age-specific hypertension prevalence were obtained from the Scottish Public Health Observatory (2018) and for high income countries from Mills et al (Circulation 2016). Individuals were considered to be on hypertension treatment if they had at least 6 months of 2011 covered by their antihypertensive prescriptions. Cardiovascular deaths from 2012–2016 were obtained from mortality records through record linkage. Generalised estimating equations (GEE) were used to assess the relationship between proportion of untreated hypertension and CV mortality. Results: The estimated number of hypertensives was 308, 208 (35.9%) and the numbers treated and untreated were 181, 662 (58.9%) and 126, 546 (41.1%) respectively. Age-stratified analyses showed the highest proportion of untreated hypertensives was in the 30–40-year (72%) and 40–50 year (58%) age groups while the lowest proportion was the 70–80 year group (28%). Figure. No caption available. Stratification by SIMD showed SIMD 1 (least deprived group) had the lowest proportion of untreated hypertensives (34%) while the most deprived groups 4 and 5 had 49% and 43% respectively. Cardiovascular mortality rates increased with each decade of life -0.95/1000 among 30–40 years old group and rising to 233/1000 in the 80+ age group. These results were maintained even after adjusting for age and SIMD using GEE. Conclusions: Estimating prevalence of untreated hypertension in the Greater Glasgow and Clyde region do not show correlation with five-year cardiovascular mortality. This discrepancy indicates more accurate estimation of hypertension prevalence and treatment using home BP is required for formulating effective health policies on hypertension.